Optimizing Health Professions Education through a Better Understanding of "School-Supported Clinical Learning": A Conceptual Model - Malou Stoffels; Saskia M. Peerdeman; Hester E. M. Daelmans; Stephanie M. E. van der Burgt; Rashmi A. Kusurkar (MDPI AG, 2023)
Interventions connecting school and clinical practice can align requirements and enhance learning outcomes. Current models and theories of clinical learning leave gaps in our knowledge about how learning processes and outcomes can be optimized by schools. In this paper, we discuss findings about threats and opportunities in the use of school standards, tools, and support in clinical learning, including underlying mechanisms, in the context of nursing education. Opportunities include competency frameworks that can challenge students to push their limits despite a task-oriented ward culture. Assignments and tools can deepen students' understanding of patient care, help them compare different experiences and stimulate self-regulated learning. Threats include rigid performance criteria that guide students' selection of learning opportunities, extensive written formats, and individualization of self-regulated learning. These threats can lead to added workload and disengagement. Based on the critically constructed argument that the role of schools in clinical learning should be acknowledged in the literature, we present a conceptual model to do so. The use of this model provides design principles for learning environments at the interface of school and practice within health professions education. Eventually, learning outcomes can be achieved efficiently without unnecessary interference with students' engagement in patient care and student-supervisor interactions.